PENGARUH MOBILISASI DINI PADA PASIEN POST SECTIO CAESAREA TERHADAP PENYEMBUHAN LUKA OPERASI DI RUANGAN NIFAS RSUD. DR. M.M DUNDA LIMBOTO - Harismayanti Harismayanti; Anik Retni (-, 2021)
The aim of this research is to know the effect of early mobilization on post-sectio caesarea patient on surgical wound healing in hospital room Dr. M.M. Dunda Limboto.The research design used Pre-experiment Experimental One group pre and post test design. The sample used as many as 14 people post-sectio caesare mother.The study was determined by actidental sampling technique. The data collection tool uses an observation sheet. Results The condition of surgical wound prior to early mobilization was 1.93. The operating wound conditions after early mobilization were 0.29. There is an effect of early mobilization in post-sectio caesarea patients on surgical wound healing. It is suggested to hospital to emphasize the implementation of early mobilization by post-sectio caesarea mother to avoid infection.